2019
DOI: 10.1007/s11306-019-1577-3
|View full text |Cite
|
Sign up to set email alerts
|

Compound danshen dripping pills normalize a reprogrammed metabolism of myocardial ischemia rats to interpret its time-dependent efficacy in clinic trials: a metabolomic study

Abstract: IntroductionClinical trials of Compound danshen dripping pills (CDDP) indicated distinct improvement in patients with chronic stable angina. Daily fluctuation of therapeutic effect agreed with a peak-valley PK profile during a 4-week CDDP regimen, but stabilized after 8-week treatment.ObjectivesThis article aims to explore the underlying mechanism for the time-dependent drug efficacy of the up-down fluctuation or stabilization in clinic trials.MethodsA rat model of myocardial ischemia was established via isopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…T 89 [also known as cardiotonic pills (CP), compound Danshen dripping pills in Chinese] is a widely used traditional Chinese medicine in China for treating ischemic angina pectoris, which consists of salvia miltiorrhiza (SM), panax notoginseng (PN), and Borneol. T 89 has passed phase II and is undergoing phase III clinical trials for prevention and treatment of ischemic cardiovascular disease by the United States Food and Drug Administration since 2016 ( Aa et al, 2019 ). Guo et al (2016) observed that T 89 pretreatment increased energy production and regulated the dominant energy metabolism mode accomplished with enhancing a metabolic shift toward fatty acid metabolism from glycolysis induced by ISO, which indicated that the regulation of energy metabolism was involved in the underling mechanism whereby T 89 exerted effect on myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…T 89 [also known as cardiotonic pills (CP), compound Danshen dripping pills in Chinese] is a widely used traditional Chinese medicine in China for treating ischemic angina pectoris, which consists of salvia miltiorrhiza (SM), panax notoginseng (PN), and Borneol. T 89 has passed phase II and is undergoing phase III clinical trials for prevention and treatment of ischemic cardiovascular disease by the United States Food and Drug Administration since 2016 ( Aa et al, 2019 ). Guo et al (2016) observed that T 89 pretreatment increased energy production and regulated the dominant energy metabolism mode accomplished with enhancing a metabolic shift toward fatty acid metabolism from glycolysis induced by ISO, which indicated that the regulation of energy metabolism was involved in the underling mechanism whereby T 89 exerted effect on myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…The normal control group ( n = 8) remained undisturbed. Subsequently, the CUMS-induced rats were injected with ISO (8 mg/kg) for five days to form the CHD model ( Aa et al, 2019 ; Hu et al, 2020 ). The rat model for CHD with depression induced by CUMS and ISO was evaluated by measuring rat body weight change, open field test, sucrose preference test, and ST-segment of the electrocardiogram.…”
Section: Methodsmentioning
confidence: 99%
“…Missing data were excluded before the analysis. After normalization against the IS, the data were evaluated using SIMCA-P 14.1 software (Umetrics, Umeå, Sweden) (21).…”
Section: Multivariate Statistical Analysismentioning
confidence: 99%